The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1982
DOI: 10.1128/jcm.16.4.637-640.1982
|View full text |Cite
|
Sign up to set email alerts
|

Survey of the extrachromosomal gene pool of Clostridium difficile

Abstract: Pseudomembranous colitis, a severe diarrheal disease, has been linked to the administration of antibiotics and to two toxins produced by Clostridium difficile. Eighty-two strains of C. difficile isolated from humans and hamsters were assayed for the presence of plasmid DNA. Agarose gel electrophoresis of Sarkosyl-lysed cells indicated that 18% of the strains contained from one to four plasmids. The plasmid DNA in these strains ranged in molecular weight from 2.7 x 106 to 60 x

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(12 citation statements)
references
References 28 publications
(20 reference statements)
0
12
0
Order By: Relevance
“…The standard cytotoxicity and antibody neutralization assays were performed to test toxin activity using chinese hamster ovary (CHO) cells as described previously [8,9]. Toxic activity was expressed as the greatest dilution that caused 50% cell death.…”
Section: Cytotoxic Assaysmentioning
confidence: 99%
“…The standard cytotoxicity and antibody neutralization assays were performed to test toxin activity using chinese hamster ovary (CHO) cells as described previously [8,9]. Toxic activity was expressed as the greatest dilution that caused 50% cell death.…”
Section: Cytotoxic Assaysmentioning
confidence: 99%
“…This bacterium is considered to be the main agent of nosocomially acquired diarrhea among adults [2]. Many various typing methods have been developed to investigate nosocomial outbreaks of C. di¤cile, some based on phenotype (lysotyping [3], serogroup-ing [4], SDS-PAGE [5], immunoblotting [6]) and others on genotype (plasmids [7], REA [8], ribotyping [9], PFGE [10], RAPD [11]). Recently, Kostman et al developed a method of PCR-ribotyping that was shown to be reproducible, easy to perform and cost-e¡ective [12].…”
Section: Introductionmentioning
confidence: 99%
“…When isolates from 35 geographically different sources were tested, 24 (66%) had plasmids, i.e., were typeable. Muldrow et al (19) found that only 18% of the 82 strains they analyzed carried plasmids. The plasmids ranged from 2.7 to 60 MDa in size.…”
Section: Discussionmentioning
confidence: 99%